2018
DOI: 10.4103/0366-6999.235113
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Homozygous Splice-Site Mutation in SCARB2 that Causes Progressive Myoclonus Epilepsy with or without Renal Failure

Abstract: Background:Progressive myoclonus epilepsies (PMEs) comprise a group of rare genetic disorders characterized by action myoclonus, epileptic seizures, and ataxia with progressive neurologic decline. Due to clinical and genetic heterogeneity of PMEs, it is difficult to decide which genes are affected. The aim of this study was to report an action myoclonus with or without renal failure syndrome (EPM4) family and summarize the clinical and genetic characteristics of all reported EPM4 patients.Methods:In the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Tonin et al identified a newly discovered synonymous c.363A>G (Gly82Gly) mutation in the β-glucosidase (GBA) gene in a type 3 Gaucher disease patient that causes the loss of an exon splicing enhancer (17). He et al revealed a novel c.995-1G>A homozygous splicing mutation in the SCARB2 gene in two PME patients that leads to loss of function of the SCARB2 protein (18).…”
Section: Discussionmentioning
confidence: 99%
“…Tonin et al identified a newly discovered synonymous c.363A>G (Gly82Gly) mutation in the β-glucosidase (GBA) gene in a type 3 Gaucher disease patient that causes the loss of an exon splicing enhancer (17). He et al revealed a novel c.995-1G>A homozygous splicing mutation in the SCARB2 gene in two PME patients that leads to loss of function of the SCARB2 protein (18).…”
Section: Discussionmentioning
confidence: 99%